The Science behind Indian Rituals, Customs and Traditions - K, Jayalakshmi (IJRDO - Journal of Social Science and Humanities Research, 2020)
Every tradition or custom would not have been practiced without having significance. The generation today looks at traditions to be based on pure beliefs. From time immemorial, Indians have observed numerous rituals and traditions from dawn to dusk in their day to day life. Some are pointed out in Vedic scriptures and some were included later during the ages of Brahman scriptures. In Indian society, these rituals were and are followed religiously, tagging it with superstition. It's high time we realize that our forefathers were way more visionary and intelligent than what we are. Religion and science are not opposing streams. There is a strong connection between them. With the advent of science and technology, we have found scientific reasons behind these rituals and traditions. Traditions and customs were taught at a very young age and followed as part of life.  In this modern age of globalization, the existing challenge is an attempt to bridge traditions and Science. This article sums up the rituals, customs and traditions with the possible scientific reasons and significance they carry with them.   Keywords— Etiquette, Indian Rituals, Pandemic, Samsara’s, Science.